The Values Theorists' Approach to Moral Citizenship Education. - Research for Better Schools, Inc., Philadelphia, PA.; Research for Better Schools, Inc., Philadelphia, PA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1978)
The document contains a paper on the values theorists' approach to moral/citizenship education and three critiques of the paper. The paper discusses the common goal of values education approaches which is to help individuals lead personally satisfying lives and become constructive members of society. Values clarification, moral development, and cognitive-decision-making theories are examined as well as the traditional models of moralizing and modeling. The author proposes a synthesis of values education objectives. Further research activities are suggested, with an emphasis on furthering knowledge of each of the separate approaches and in undertaking major integrative studies which address basic issues in the field. The final section briefly examines the general community reaction to values education. The first critique takes issue with the proposed synthesis of values education theories and with the author's slighting the social context of values education. The final critique contends that the author of the main paper assesses the state of the art in values education with optimism clouded by uncritical eclecticism. (KC)
Availability: Research for Better Schools, Inc., 444 North Third Street, Philadelphia, PA 19123 ($6.00).
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Contract Number: OB-NIE-78-0207.
ERIC Note: For related documents, see SO 012 131-133; Paper presented at Moral/Citizenship Education Conference (Philadelphia, PA, June 4-6, 1976).
Educational level discussed: Elementary Secondary Education.
May also be available online. Address as at 14/8/18
Keywords: Citizenship; Citizenship Education; Curriculum Development; Educational Philosophy; Educational Theories; Elementary Secondary Education; Ethical Instruction; Moral Development; Moral Values; Research Needs; Speeches; Values; Speeches/Meeting Papers; Opinion Papers